Review on microbial chitosan for the fabrication of piezoelectric thin film - Hazmi, Alia Tasnim; Ahmad, Farah; Mohd Hatta, Maziati Akmal; Md Ralib, Aliza Aini (2020)
Chitin has proven to have a good mechanical and electrical properties to be used in making piezoelectric thin films. However, due to the restriction in solubilizing chitosan in many solvents, there is increasing interest in exploring the used of chitosan in producing thin films. Chitosan, compared to chitin, can be easily solubilized in certain dilute acids. Chitosan that has been extracted from fungal biomass can be used for the fabrication of biomaterial thin films. There are different ways that can be used to fabricate a thin film such as electrospinning, spin-coating, solvent casting and also the hot press technique.